Assessment of Causal Direction Between Gut Microbiota and Inflammatory Bowel Disease: A Mendelian Randomization Analysis - Zhang, Zi-Jia; Qu, Hong-Lei; Zhao, Na; Wang, Jing; Wang, Xiu-Yan; Hai, Rong; Li, Bin (Frontiers in Genetics, 2021)
Background Recent studies have shown that the gut microbiota is closely related to the pathogenesis of ulcerative colitis (UC), but the causal nature is largely unknown. The purpose of this study was to assess the causal relationship between intestinal bacteria and UC and to identify specific pathogenic bacterial taxa via the Mendelian randomization (MR) analysis. Materials and Methods A genome-wide association study (GWAS) summary statistics based two-sample MR analysis was performed. Summary statistics of microbiome GWAS in 1,126 twin pairs of the TwinsUK study was used as exposure. Summary statistics of the UC GWAS in 48,328 British of the UK inflammatory bowel disease (UKIBD) and Understanding Social Program (USP) study were used as discovery sample of outcome, and GWAS in 35,289 participants from British IBD study were used as replication, respectively. Bacteria were grouped into taxa features at both family and genus levels. Results In the discovery sample, a total of 30 bacteria features including 15 families and 15 genera were analyzed. Three features were nominally significant, including 1 family (Verrucomicrobiaceae, 2 SNPs, beta=-0.04, p=0.05) and 2 genera (Akkermansia, 2 SNPs, beta=0.04, p=0.05 and Dorea, 2 SNPs, beta=-0.07, p=0.04). One family and two genera Verrucomicrobiaceae and Akkermansia and Dorea was successfully replicated in the replication sample (Verrucomicrobiaceae and Akkermansia: Pdiscovery=0.05, Preplication=0.02, Dorea: Pdiscovery=0.04, Preplication=0.01). Conclusions Our findings provided evidence for the causal relationship from gut microbiota to the pathogenesis of IBD, as well as identified specific pathogenic bacteria, thus offered new sights into the mechanism of IBD development.